Secreted aspartyl protease 3 regulated by the Ras/cAMP/PKA pathway promotes the virulence of Candida auris - Kim, Ji-Seok; Lee, Kyung-Tae; Bahn, Yong-Sun (Frontiers in Cellular and Infection Microbiology, 2023)
The surge of multidrug-resistant fungal pathogens, especially Candida auris, poses significant threats to global public health. Candida auris exhibits resistance to multiple antifungal drugs, leading to major outbreaks and a high mortality rate. With an urgent call for innovative therapeutic strategies, this study focused on the regulation and pathobiological significance of secreted aspartyl proteinases (SAPs) in C. auris, as these enzymes play pivotal roles in the virulence of some fungal species. We delved into the Ras/cAMP/PKA signaling pathway’s influence on SAP activity in C. auris. Our findings underscored that the Ras/cAMP/PKA pathway significantly modulates SAP activity, with PKA catalytic subunits, Tpk1 and Tpk2, playing a key role. We identified a divergence in the SAPs of C. auris compared to Candida albicans, emphasizing the variation between Candida species. Among seven identified secreted aspartyl proteases in C. auris (Sapa1 to Sapa7), Sapa3 emerged as the primary SAP in the pathogen. Deletion of Sapa3 led to a significant decline in SAP activity. Furthermore, we have established the involvement of Sapa3 in the biofilm formation of C. auris. Notably, Sapa3 was primarily regulated by Tpk1 and Tpk2. Deletion of SAPA3 significantly reduced C. auris virulence, underscoring its pivotal role in C. auris pathogenicity. The outcomes of this study provide valuable insights into potential therapeutic targets, laying the groundwork for future interventions against C. auris infection.